POSTMODERNISME DALAM SUPERNOVA (AKAR) KARYA DEWI LESTARI - Inung Setyami (CARAKA, 2020)
Â The research is focused on problems related to postmodern and postmodern studies. The data source in this study was the second episode of Supernova's novel, Akar, the first printed in 2002. The data were obtained by reading and taking notes. Analyzed by qualitative descriptive analysis techniques. The validity of the data is obtained through validity (semantic and referential) and reliability (interrater and intrarater). The results showed that Supernova: Akar is a postmodern work. Postmodernism in Supernova, namely: (1) The attitude of characters who long for locality and are disgusted by the establishment and freedom of the western world in the high-level modern era; (2) The emergence of primitivism, namely nomadic life at the peak of modern life; (3) The presenting of a supernatural world concerning a creature whose existence is visible to the eye but exists, namely a supernatural being; (4) The existence of an unclear place where its location and description is ontological dominant; (5) There is a method of "physical renewal or body shape", namely the addition of metal to the horned head, as a lifestyle; (6) The existence of a dream world which is also a real world.